‘Alāqatu Ta‘līmi Kitābi “al-Ghāyah wa at-Taqrīb” bi Khazīnati al-Mufradāt (Dirāsah Kammiyyah li al-Madrasah ad-Dīniyyah fī al-Ma‘had Dār al-Falāḥ 5 Cukir Jombang - Alfiyatul Laily Hidayah; Lailatul Qomariyah (Program Studi Pendidikan Bahasa Arab, 2022)
This research examines, 1) How the form of learning the book al-Ghoyah wa at-Taqrib madrasah diniyah in Darul Falah Islamic boarding school 5 Cukir Jombang?. 2) How do the Vocabulary of madrasah iniyah students repository in Darul Falah Islamic boarding school 5 Cukir Jombang?. 3) How is the relationship between learning the book al-Ghoyah wa at-Taqrib with the treasury of Vocabulary Madrasah Diniyah students in Darul Falah Islamic boarding school 5 Cukir Jombang?. The method in this research is quantitative research with a correlational type. Data collection was carried out by using observation techniques, tests and questionnaires, and documentation. Then analyzed by the Spearman Rank correlation formula. The results of this study: 1) learning the book al-Ghoyah wa at-Taqrib madrasah diniyah at the Darul Falah Islamic boarding school 5 Cukir Jombang is carried out every afternoon on Thursday with the teaching methods bandongan, halaqoh and rote memorization. The textbook used is the book al-Ghoyah wa at-Taqrib written by al-Qhadi Abi Syuja'. 2) The treasury of Vocabulay of madrasah diniyah students in Darul Falah Islamic boarding school 5 Cukir Jombang in general is still not maximally known to students. This was evidenced by the results of the oral test that have been carried out. 3) There is no relationship between variables X and Y which means there is no relationship between learning the book al-Ghoyah wa at-Taqrib and the vocabulay treasury. This was evidenced by the results of hypothesis testing with a sig value of 0.645, which means (Ho) is accepted and (Ha) is rejected. It’s mean that there is no relationship between learning the book al-Ghoyah wa at-Taqrib with the vocabulary treasury. This is due to the lack of vocabulary owned by students and a lack of interest in learning in the field of Arabic.